STRATEGIES FOR NURTURING THE COMMUNITY IN ADDRESSING WORSHIP DEGRADATION AMONG THE PINARIK COMMUNITY IN THE DOLOK SIGOMPULON SUBDISTRICT, NORTH PADANG LAWAS REGENCY - Muktarruddin; Ilham Mirzaya Putra; Ritonga, Mardina Ratna Sari (KOMUNITAS, 2023)
The aim of this research is to determine the degradation of worship that occurs in Pinarik Village, Dolok Sigompulon District, North Padang Lawas Regency. As well as researching strategies for developing people in overcoming the degradation of worship in the community of Pinarik Village, Dolok Sigompulon District, North Padang Lawas Regency. This type of research is qualitative with a qualitative descriptive approach method. The results of the research show that the degradation of community worship in Pinarik Village is very worrying, especially in prayer, fasting and morals. The degradation of worship is caused by a lack of awareness among the public regarding the importance of carrying out worship. So that community leaders carry out strategies for developing people in overcoming the degradation of worship in the Pinarik community through several strategies, namely: strategies for giving advice, strategies for example, strategies for habituation and strategies for giving punishment.